REPORT OF THE 1951 PRESIDENT. - Garner, S. Paul (The Accounting Review, 1952)
While there have been few spectacular happenings during the year 1950, steady progress is evident on all sides. There has been a substantial increase in the membership and the financial condition of the American Accounting Association continues to be satisfactory. The Association owns sufficient securities to enable it to survive a period of stress caused by war or other conditions. Nearly 500 members and guests attended the annual convention held at the University of Denver. This was one of the largest groups ever to attend a convention of the Association. The periodical "The Accounting Review," under the editorship of Frank P. Smith, has continued to serve instructors, students and practitioners with a series of significant and helpful articles, book reviews, solutions to Certified Public Accountant examination problems and news items of members of the Association. It has an impressive international reputation as a scholarly publication in the field of accounting. One of the greatest satisfactions received is from the splendid cooperation of committee members. Around one hundred and sixty members of the Association have contributed generously of their time in the conduct of its committee activities.